Sclerosing Lipogranuloma of the Penis Secondary to Olive Oil: Case Report - Velázquez-Viniegra, Itzel; Figueroa-Araujo, Demián; Flores-López, Alejandro Alberto; Ramírez-Jiménez, Daniela Isabel; Cano-García, Maria Ximena; Almeida-Navarro, José Samuel; Padrón-Arredondo, Guillermo (British Journal of Healthcare and Medical Research, 2023)
Introduction: Chronic granulomatous inflammation can develop after injecting sclerosants, such as foreign oily substances, into the penis. The disorder primarily affects the administration site, but regional lymphadenopathy may appear to be a systemic disease. Clinical Case: A 25-year-old male patient, single with grade I obesity and initially from Nayarit, Mexico. He started his current condition three months ago after injecting olive oil into the penis to increase its thickness. Subsequently, he went to the general practitioner to present a picture of partial urinary obstruction after one week of evolution due to the increased volume of the foreskin, for which his doctor decided to cut the foreskin to free the glans penis and thus resolve the obstructive picture. Discussion: Paraffinomas result from an injection of a foreign substance that contains a linear chain of saturated hydrocarbons, such as mineral oil or paraffin. The body lacks the enzymes to metabolize the interstitial exogenous oils; consequently, a foreign body reaction occurs. Patients often present with penile deformity because the oil and subsequent granuloma cannot extend beyond the standard anatomical planes of the genitalia. The foreign body reaction manifests in inflammation and induration, edema, scarring, necrosis, deformity, ulceration, painful erections, and, eventually, the inability to perform sexual activities. Reactive lymphadenopathy of the region develops, and gross deformity can lead to clinical confusion with a misdiagnosis of neoplastic and often warrants biopsy.